2011
DOI: 10.1007/s13361-011-0231-8
|View full text |Cite
|
Sign up to set email alerts
|

High Throughput Enzyme Inhibitor Screening by Functionalized Magnetic Carbonaceous Microspheres and Graphene Oxide-Based MALDI-TOF-MS

Abstract: In this work, a high throughput methodology for screening enzyme inhibitors has been demonstrated by combining enzyme immobilized magnetic carbonaceous microspheres and matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) with grapheme oxide as matrix. First, model enzyme acetylcholinesterase (AChE) was immobilized onto the 3-glycidoxypropyltrimethoxysilane (GLYMO)-modified magnetic carbonaceous (MC) microspheres, displaying a high enzyme activity and stability, and also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…For label-free enzyme activity assay, GO was employed as matrix to analyze substrates and products of enzyme, detecting molecular weight changes before and after enzyme reactions. Liu et al suggested the highly efficient acetylcholinesterase (AChE) assay platform by utilizing GO and functionalized magnetic carbonaceous (MC) microspheres [136]. The substrate and product were easily separated from AChE immobilized onto the MC microspheres and analyzed by LDI-MS using GO as matrix.…”
Section: Ldi-ms-based Assay Platformmentioning
confidence: 99%
See 1 more Smart Citation
“…For label-free enzyme activity assay, GO was employed as matrix to analyze substrates and products of enzyme, detecting molecular weight changes before and after enzyme reactions. Liu et al suggested the highly efficient acetylcholinesterase (AChE) assay platform by utilizing GO and functionalized magnetic carbonaceous (MC) microspheres [136]. The substrate and product were easily separated from AChE immobilized onto the MC microspheres and analyzed by LDI-MS using GO as matrix.…”
Section: Ldi-ms-based Assay Platformmentioning
confidence: 99%
“…Liu et al established a high-throughput methodology for inhibitor screening acetylcholinesterase (AChE) using GO-based LDI-MS analysis [136]. By combining the magnetic microspheres for AChE immobilization and GO as matrix, this platform presented simple, cost effective, and efficient performance, which are important characteristics to be utilized for large-scale inhibitor screening.…”
Section: Applications Of Go-based Biosensors In High-throughput Screementioning
confidence: 99%
“…Notably, GO is easier to obtain than oxidized CNTs because it is actually an intermediate in the synthesis of graphene from graphite by chemical methods. Therefore, a number of papers have reported the application of GO as a matrix or a probe for MALDI or SELDI MS [66,[73][74][75][81][82][83]. Whether graphene or GO shows better performance in LDI MS seems to be associated with the nature of the target analytes [66,[73][74][75].…”
Section: Graphenementioning
confidence: 99%
“…[1][2][3] To achieve these objectives, several enzyme inhibitor assay-related approaches have been reported. [4][5][6][7][8][9][10][11][12][13] In enzyme inhibitor assays, high-performance liquid chromatography (HPLC) with ultraviolet (UV) detection, and capillary electrophoresis (CE) are widely used as analytical methods. 14 The HPLC-UV methods [15][16][17] require a complex operation, long elution time, and a large volume of organic solvents.…”
Section: Introductionmentioning
confidence: 99%